Equity and Inclusion in Higher Education - Salmi, Jamil (International Higher Education, 2023)
Around the world, many young people face challenging circumstances beyond their own control, due to discrimination on the grounds of race, gender, sexual orientation, geographical origin, socioeconomic background, or other attributes, which drastically affect their opportunities to access higher education and graduate successfully. This article reviews the scope of disparities, assesses the equity impact of COVID-19, and outlines the main elements of effective national- and institutional-level equity promotion policies.